A comparison of self-reported to cotinine-detected smoking status among adults in Georgia. - Williams, Julianne; Rakovac, Ivo; Loyola, Enrique; Sturua, Lela; Maglakelidze, Nino; Gamkrelidze, Amiran; Mauer-Stender, Kristina; Mikkelsen, Bente; Breda, João (European Journal of Public Health, 2020)
Background Self-reported measures of tobacco use may have limited validity, particularly among some populations. This study aims to validate self-reported smoking measures among Georgian adults participating in the 2016 STEPS survey using cotinine biomarker measurements, and to explore potential differences according to sociodemographic characteristics. Additionally, this paper examines how the estimated prevalence of smoking in the population varies according to measurement type. Methods Using the WHO standardized STEPS methodology, adults self-reported their smoking status. In a later stage of the survey, a subset of participants provided a urine sample, which was tested for cotinine. Using each participant's objective cotinine measurement and their self-reported smoking status, we calculated the sensitivity, specificity and positive predictive value of self-reported smoking. Next, we calculated the estimated prevalence of smokers according to the type of measurement. Results Results indicated high sensitivity (83.37%, 95% CI: 76.79–88.37%) among males and relatively low sensitivity (38.60% CI: 29.23–48.90%) among females. According to self-report, the prevalence of smokers was 26.44% (23.61–29.48%), while according to cotinine detection, the prevalence of smokers was 32.27% (29.16–35.55%). Among all subgroups, the self-reported prevalence of smoking was significantly lower than the cotinine-detected prevalence. Conclusions To the best of our knowledge, this is the first time that the validity of the STEPS self-reported tobacco indicator has been tested. Self-reported measures of smoking status may lead to an under-estimation of smoking prevalence among Georgian adults, especially women. These findings suggest that integration of biochemical measures of smoking into tobacco use studies may be an important investment.